The effect of 660nm light-emitting diode irradiation on human gingival fibroblast cell proliferation - JiaQi, Wang (Universiti Sains Malaysia, 2025)
Light therapy has become a common treatment modality in various medical fields, including dermatology, dentistry, and cosmetics. This study aimed to evaluate the effect of 660 nm ligh-emitting diode on the proliferation and viability of human gingival fibroblasts in vitro. The cells were irradiated with 660nm light-emitting diode for 60 and 120 seconds 24-hours post-seeding. After 24- and 48-hours irradiation, cell count, and viability were determined. The results then were analysed using a one-way ANOVA test (p < 0.05). The findings revealed a significant increase in cell proliferation rate and viability in the irradiated groups compared to the control group, with the 120 seconds irradiation group showing the highest enhancement at both time points. These results suggest that 660 nm LED light can effectively promote the proliferation and viability of human gingival fibroblasts, highlighting its potential as a valuable tool in regenerative dentistry and periodontal therapy